The Credit Crunch and Insider Trading. Issue 2 (May 2014) - Tavakoli, Manouchehr; McMillan, David; McKnight, Phillip J.
<x xml:space="preserve">Abstract</x> This paper examines the behaviour and information content of insiders' trades before and after the credit crunch and, in particular, examines the extent to which some insiders anticipated the market crash and took action to protect their positions. In part, the market crash was brought about by the excessive borrowing of financial institutions. Our results point to the view that a number of insiders, primarily directors, were aware that the excessive use of leverage by financial institutions would ultimately have a detrimental impact on the economy. These insiders acted by selling their shares prior to the market collapse and subsequently buying them back at a lower price. Supportive evidence for the above view is provided through both graphical evidence and regression analysis. In particular, we demonstrate a link between insider behaviour and the rapid decline in share values. Further evidence is also provided of a link between insider behaviour and future risk as measured by the CDS premium. In short, we argue that this selling was not motivated by liquidity or other contrarian strategies but was a result of understanding how higher levels of leverage and excessive trading in new risky derivatives could lead to higher levels of risk, an insight possessed only by a subset of insiders.